The Role of Nutrition on the Immune Response - Felisha Febriane Balafif; Anggun Rafisa; Faisal Kuswandani; Nuroh Najmi (Jurnal EduHealth, 2023)
The immune system reaction against infections and other foreign substances is known as the immune response. Nutrition is a critical component in the modulation of the immune system, hence the importance of a balanced diet. Better nutrition improves health, reinforces the immune system, contributes to longevity, and decreases the chance of non-communicable diseases. Thus, nutrition, health, and immune system are strongly connected. The aim of the present study is to evaluate current knowledge on the role of nutrition on the immune response. The article was conducted of two databases and were limited to the period from January 2018 to April 2023 with a combination of the following keywords: “role" and "nutrition" and "immune response. The results obtained were 17 articles found at the beginning of the search in both databases, and the 10 full text articles were selected for further review and discussion. The results of this study shows that immunonutrition plays a role in immune function. Nutrition such as vitamins A, B6, B12, C, D, E, and folate; and trace elements (zinc, iron, selenium, magnesium, and copper) play important and complementary roles in supporting both the innate and adaptive immune systems. The development and maintenance of our immune system are very intricately tied to our dietary pattern. Therefore, working on our food habits and improving our nutrition seem to be a pragmatic approach to strengthen our immune response. Multiple micronutrients play vital roles in supporting the immune response.